Intracystic Papillary Carcinoma of the Breast - Burton, Élan C. (Radiol Case Rep, 2015)
We present the case of a 63-year-old woman with intracystic papillary carcinoma of the breast who presented with a palpable mass, one year after a negative mammogram. Sonography showed a complex mass and ultrasound-guided aspiration cytology was negative, and the patient returned 6 months later with a recurrent mass. Excisional biopsy revealed invasive intracystic papillary carcinoma. Intracystic papillary carcinoma is a rare malignancy of the breast primarily affecting postmenopausal women. As opposed to invasive micropapillary carcinoma, intracystic papillary carcinoma is a low-grade carcinoma with a favorable prognosis.